A laboratory study of Portland cement hydration under low temperatures. (10th July 2017) - Liu, Zhuangzhuang; Sha, Aimin; Hu, Liqun; Zou, Xiaolong
Abstract : Portland cement hydration is related to mechanical properties, durability and sustainability of cement concretes, and also to the service level of building and structures. This paper will report an initial understanding of Portland cement hydration under low temperatures based on several laboratorial investigations (e.g. thermal gravity analysis /derivative thermogravimetry and X-ray diffraction). Mechanical behaviours and phase evolution are discussed in this report. Calculation based on Powers' model in cement hydration was also utilised to analyse the Portland cement hydration process under low temperatures. Research shows that low temperature slows the hydration reaction rate and delays the initial setting time, as a result the mechanical behaviours are also influenced. The mechanical behaviours evolution was in great agreement with the calcium silicate hydrate fraction calculated by Powers' model.